Respostas
respondido por:
0
6(x - 2) = 12
6x - 12 = 12
6x = 12 + 12
x = 24 / 6
x = 4
6x - 12 = 12
6x = 12 + 12
x = 24 / 6
x = 4
respondido por:
0
6.(x-2)=12
6 x + 12 = 12
6 x = 12 - 12
6 x = 0
x = 0 / 6
x = 0
perceba que depois da distributiva fica
6 x + 12 = 12
6 * 0 + 12 = 12
0 + 12 = 12
12 = 12
x = 0 está correto
espero ter ajudado
6 x + 12 = 12
6 x = 12 - 12
6 x = 0
x = 0 / 6
x = 0
perceba que depois da distributiva fica
6 x + 12 = 12
6 * 0 + 12 = 12
0 + 12 = 12
12 = 12
x = 0 está correto
espero ter ajudado
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás